TEACHING IN PANDEMIC: TEACHERS’ EXPERIENCES DURING CORONAVIRUS OUTBREAK - Pipit Muliyah; Dyah Aminatun; Linda Septiyana (Universitas Teknokrat Indonesia, 2022)
In 2020, novel coronavirus or Covid-19 spread rapidly via international air travel from China to many cities across the world, and it is resulting in over a million cases of infections and deaths. In Indonesia, as the virus invaded the community so did fear. This paper used a case study to investigate teachers’ experiences of the role played by digital technology. The interview and questionnaire results showed that teachers were faced with the challenge of using digital technology to provide an education that would reach beyond school walls into the homes and computers of Indonesian students. Teachers had to re-think their teaching strategies and provide their students with new and different opportunities to work through curriculum requirements. Covid-19 provided a catalyst for the intense use of ICT in ways that had not been anticipated or prepared for. The plunge into ICT was a voyage of exciting discovery for some and frustration for others. Either way, it had an impact on subsequent perceptions of the potential and shortcomings of ICT in education in Indonesia.